Comparison of gut microbiota immunity and pathology in specific-pathogen-free chickens with glandular and muscular gastritis using different methods - Yan, Zunxiang; Yang, Shifa; Lin, Shuqian; Zhao, Zengcheng; Liu, Yueyue; Yin, Bin; Yi, Yunpeng; Song, Shikai; Zhang, Rongling; Huang, Zhongli (Frontiers in Veterinary Science, 2024)
The objective of this study is to compare several different methods in order to screen the optimal model for preventing and treating chicken glandular and muscular gastritis syndrome. Twenty-four 40-day old specific pathogen free (SPF) chickens were randomly allocated into 4 groups (N=6): polyethylene glycol + ammonium chloride group (M1 group), acetic acid + rhubarb group (M2 group), polyethylene glycol + rhubarb group (M3 group), and control group. The control group had free access to water, while the remaining groups received different doses of molding reagents added to their drinking water. The animal models were assessed based on clinical manifestations, histopathology findings, serological analysis, and composition of intestinal microbiota in order to establish an optimal approach for constructing the avian model of glandular and muscular gastritis. The SPF chickens in each model group exhibited typical symptoms of glandular and muscular gastritis, poor spirit, yellow loose stools with undigested feed, and enlargement and ulceration of the glandular and muscular stomach. Among these groups, the M3 group had the highest incidence rate of 100%. In comparison to the control group, the body weight and body temperature of the chicken in three model groups were reduced, the glandular and muscular stomachs, and duodenum showed different degrees of bleeding, mucosal abscission and other pathological injuries. Additionally, the levels of serum IL-2 and α-amylase activity decreased, while the content of IL-4 increased. After conducting 16s rDNA sequencing, it was observed that the abundance of Bacteroides, Faecalibacterium, and Ruminococcaceae UCG-014 significantly increased in the model group compared to the control group. Conversely, there was a notable decrease in the levels of Megamonas and Lactobacillus, which are speculated to be associated with arachidonic acid metabolism, the NF-κB signaling pathway, and TNF signaling pathways. The combination of polyethylene glycol and rhubarb has emerged as the most effective method for establishing the glandular and muscular gastritis model in SPF chickens. This constructed chicken model displayed distinct signs of damage to the glandular and muscular stomach, inflammatory response, and disturbance in intestinal flora, thereby providing a foundation for future research on the prevention and treatment of this syndrome.